Blockable Zn10L15 Ion Channels through Subcomponent Self‐Assembly. Issue 48 (3rd November 2017) - Haynes, Cally J. E.; Zhu, Jinbo; Chimerel, Catalin; Hernández‐Ainsa, Silvia; Riddell, Imogen A.; Ronson, Tanya K.; Keyser, Ulrich F.; Nitschke, Jonathan R.
Abstract: Metal–organic anion channels based on Zn10 L15 pentagonal prisms have been prepared by subcomponent self‐assembly. The insertion of these prisms into lipid membranes was investigated by ion‐current and fluorescence measurements. The channels were found to mediate the transport of Cl − anions through planar lipid bilayers and into vesicles. Tosylate anions were observed to bind and plug the central channels of the prisms in the solid state and in solution. In membranes, dodecyl sulfate blocked chloride transport through the central channel. Our Zn10 L15 prism thus inserts into lipid bilayers to turn on anion transport, which can then be turned off through addition of the blocker dodecyl sulfate. Abstract : Tune in to this new channel : Zn10 L15 pentagonal prisms prepared by subcomponent self‐assembly were able to function as anion channels in phospholipid bilayers. The channels were blocked by amphiphilic dodecyl sulfate anions, which were bound by and plugged the central cavities of the channels (see picture).